Do Coffee Exports Have an Impact on Economic Growth in Indonesia? - Nasution, Nazla Atikah Hikmatias; Zahra, Zhena Nofhatiaz; Octariyadi, Nabila Umami; Sahara, Sahara (Signifikan: Jurnal Ilmu Ekonomi, 2025)
Research Originality: The novelty lies in exploring an under-researched topic, with limited studies on the impact of coffee exports from 1993 to 2024, considering key events such as the Asian financial crisis and the COVID-19 pandemic. Research Objectives:  This study examines the short-term and long-term effects of exchange rates and coffee exports on economic growth. Research Methods: This study utilizes data from 1993 to 2024 on exchange rates, coffee exports, recessions, and economic growth in Indonesia. The analysis is conducted using the ARDL model. Empirical Results: Exchange rate depreciation has a negative impact on GDP in the short term, while past depreciation has a positive effect on economic growth. The value of coffee exports has a marginal positive effect on GDP, while the volume of coffee exports shows inconsistent impacts. Recession does not significantly affect GDP, likely due to policy responses. Long-term estimates show a stable relationship among the variables, with adjustments occurring at a rate of 35.43% per period. Implications: The government should thoroughly evaluate existing policies with a focus on promoting economic growth, while enhancing the quality of Indonesian coffee exports to remain competitive globally. JEL Classification: C32, E01, F10, O11 How to Cite:Hikmatias, N.A., Zahra, Z.N., Octariyadi, N.U., & Sahara. (2025). Do Coffee Exports Have an Impact on Economic Growth in Indonesia?. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 489-504. https://doi.org/10.15408/sjie.v14i2.46425.